Prospects of Halal Industry in Indonesia: Literacy and Inclusion of Halal Products - Ismanto, Kuat; Farmawati, Ira (Islamic Studies Journal for Social Transformation, 2023)
This research aims to map the literacy and inclusion of halal products in Muslim communities and their impact on the halal industry in Indonesia. The design of this research is a field study with a mixed approach (descriptive quantitative-qualitative). The population of this research is the local residence in general and the academic community of Islamic universities in particular. The number of research respondents was 103 people obtained from distributing questionnaires via Google Forms. Because the population size is unknown, the sample was determined using the Lameshow model based on the convenience sample. From the data processing, it was concluded that literacy and inclusion of halal products among the public were categorized as high—aspects of knowledge of halal ingredients, halal products, and halal labels in the high category. Respondents' understanding and knowledge of "halal" came from ulama, the internet, social media, and others. The community's "halal" literacy in the form of use and priority of using halal products is also categorized as high. They also support the government to make "Indonesia" the world's Halal Hub. These findings, it can be understood that if literacy and community inclusion in the regions are high, it can support Indonesia to reach halal industry development.